LEBER'S DISEASE. CLINICAL CASE - N. N. Maslova; Ye. A. Andreyeva; Ye. V. Yerokhina (Бюллетень сибирской медицины, 2013)
Violation of visual functions and oculomotor frustration develop at 90% of patients with MS. More than a half of patients are transferred by the numerous recurrence of an optical neuritis which is coming to an end with a partial atrophy of optic nerve. For well-timed purpose of pathogenetic treatment differential diagnostics with other diseases, being accompanied an atrophy of an optic nerve, in particular with Leber's disease.